The peculiarities of phraseological units translation in book’s of Chingiz Aitmatov - Zilinka, M.N. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
Phraseology is a treasure of any language, in phraseology we are able to see the history of nations, their peculiarities, culture and ways of life. Phraseology belongs to “hard-to-translate” category and gives some difficulties and problems for translators. That’s why the question about translation of phraseological units is considered to be important and specific in translation studies. In translation theory there are two ways of rendering of phraseological units: phraseological (equivalent, analogue) and nonphraseological (calque, explication, antonymic translation and combined translation). Our research article is based on the works of Chingiz Aitmatov, a great writer not only of Kirgizstan but also a great writer of Kazakhstan; these works are “The Place of the Skull” and “The day Lasts More than a Hundred Years”. In this article we showed the main features and characteristics of the texts written by the author. We have analyzed different methods of rendering of phraseological units, the examples will be taken from the official translation of the novels translated by Natasha Ward and John French. At the end of the project analysis we have found out the most widely used methods of translation, which we used by expert translators, the results are shown diagrammatically